The Significance of Diabetes in Orthodontic Patients: Treatment Modalities and Considerations - Kumaran Vijayarangam (Medical Research and Its Applications Vol. 6, 2024)
The present study highlights the significance of Diabetes in Orthodontic Patients. Diabetes mellitus, often referred to simply as diabetes, is a chronic metabolic disorder that affects millions worldwide. It’s not just a medical condition; it’s a journey that transforms daily life for those living with it. The classical symptoms of hyperglycemia are polyuria, polydipsia and polyphagia, blurring of vision. In severe cases results in ketoacidosis. The etiology of diabetes mellitus is multifactorial – an interplay of genetic, epigenetic and environmental factors, primary destruction of islet cells, cancer, surgery and trauma. Orthodontic treatment was more common to be performed among adolescents and young adults. Recent advances encouraged elder individuals to seek dental clinics for orthodontic interventions.